(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The history of studying the flora of Crimea is divided into 8 periods according to standards proposed by the outstanding florists (Hablitz C.I., Pallas P.S., Bieberstein F.K., Steven C.C., Aggeenko V.N., Wulf E.V., Rubtzov N.I., Golubev V.N.). Despite of considerable changes in the list of species and subspecies, a new continuing author’s revision of the Crimean plant diversity gives the estimate that fluctuates around the level of 2700 that fits well phytogeographical rules.